2018
DOI: 10.1016/j.gore.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Associated characteristics and impact on recurrence and survival of free-floating tumor fragments in the lumen of fallopian tubes in Type I and Type II endometrial cancer

Abstract: ObjectiveThis study sought to evaluate characteristics of cases of free-floating tumor fragments within the lumen of fallopian tubes (‘floaters’) on final pathology for Type I and Type II endometrial adenocarcinoma, including relationships with disease recurrence and mortality.MethodsA single institution experience of 1022 consecutive cases of uterine cancer presenting between 2005 and 2010 was retrospectively reviewed, with data extraction from electronic medical records. Associations of floaters with baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Pathological studies indicated that the use of a uterine manipulator increased lymphovascular space invasion, the rate of positive peritoneal cytology, and the presence of free-floating tumour fragments within the lumina of the fallopian tubes. [12][13][14] However, these effects were not recognized in another research. 15,16 According to reports on oncologic outcome, the use of a uterine manipulator in laparoscopic surgery does not affect recurrence and survival.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Pathological studies indicated that the use of a uterine manipulator increased lymphovascular space invasion, the rate of positive peritoneal cytology, and the presence of free-floating tumour fragments within the lumina of the fallopian tubes. [12][13][14] However, these effects were not recognized in another research. 15,16 According to reports on oncologic outcome, the use of a uterine manipulator in laparoscopic surgery does not affect recurrence and survival.…”
Section: Discussionmentioning
confidence: 85%
“…There has been extensive debate concerning the use of uterine manipulators in endometrial cancer surgery. Pathological studies indicated that the use of a uterine manipulator increased lympho‐vascular space invasion, the rate of positive peritoneal cytology, and the presence of free‐floating tumour fragments within the lumina of the fallopian tubes 12–14 . However, these effects were not recognized in another research 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Although these observations are logical and far from negligible, their real clinical meaning has been well clarified by several studies that suggested that the use of IUM is safe in EC staging (21,40,41). However, the retrospective nature of these researches did not allow the scientific community to say a definitive word on this issue.…”
Section: Discussionmentioning
confidence: 99%